2019
DOI: 10.1103/physrevb.99.024501
|View full text |Cite
|
Sign up to set email alerts
|

Skyrmion formation due to unconventional magnetic modes in anisotropic multiband superconductors

Abstract: Multiband superconductors have a sufficient number of degrees of freedom to allow topological excitations characterized by Skyrmionic topological invariants. In the most common, clean s-wave multiband, systems the interband Josephson and magnetic couplings favours composite vortex solutions, without a Skyrmionic topological charge. It was discussed recently that certain kinds of anisotropies lead to hybridisation of the interband phase difference (Leggett) mode with magnetic modes, dramatically changing the hy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…In isotropic superconductors, domain walls are associated with zero magnetic field, unless the domain wall is attached to an inhomogeneous pinning center or there is an underlying density inhomogeneity [9,12,13]. However, in the presence of anisotropies, it has been shown that the magnetic field is coupled with phase difference gradients [15,[26][27][28] and with matter field density gradients [30]. This would suggest that anisotropies could principally alter the magnetic signatures of domain walls in s + is and s + id systems.…”
Section: Ginzburg-landau Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In isotropic superconductors, domain walls are associated with zero magnetic field, unless the domain wall is attached to an inhomogeneous pinning center or there is an underlying density inhomogeneity [9,12,13]. However, in the presence of anisotropies, it has been shown that the magnetic field is coupled with phase difference gradients [15,[26][27][28] and with matter field density gradients [30]. This would suggest that anisotropies could principally alter the magnetic signatures of domain walls in s + is and s + id systems.…”
Section: Ginzburg-landau Formulationmentioning
confidence: 99%
“…Although, in the isotropic s + is models, a straight domain wall does not produce any magnetic field [9], it was observed in Refs. [26][27][28] that in the presence of anisotropies, the phase difference between the components couples directly to the magnetic field, which could lead to domain walls exhibiting spontaneous magnetic fields in s + is states of the anisotropic materials, such as Ba 1−x K x Fe 2 As 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Skyrmions has been predicted for K 2 Fe 4 Se 5 material where superconductivity emerges at room temperature and stable Skyrmions become Cooper pairs through a quantum anomaly [15]. Further approaches have been made on this field [16][17][18][19][20] and also analogies between vortex in superconductors systems and Skyrmions in magnetic materials. Skyrmion crystal with a triangular array in magnetic systems was shown to have strong similarities with Abrikosov vortex lattice in type-II superconductors [21].…”
Section: Introductionmentioning
confidence: 99%
“…where c is some real constant and v r, * is the real part of v * . The complex magnetic field penetration length implies oscilatory decay of the magnetic field as observed in anisotropic systems without BTRS [13][14][15]. Here we find that in a p + ip superconductor one cannot assume that a perturbation of the gap fields will decay with real exponents: i.e.…”
Section: Calculation Of Length Scalesmentioning
confidence: 60%
“…While usually the magnetic (London) modes decouple from other normal modes of the system, such as density and phase difference (Leggett) modes, having different anisotropies in different bands results in a hybridization of the London mode with the phase difference mode [13][14][15]. For a sys-tem with N bands that means that magnetic field decay is described by several modes with different exponents and there could be up N + 1 such modes in the systems considered in [13][14][15]. Furthermore the powers in the corresponding exponents under certain conditions are complex leading to a damped oscillatory decay of the magnetic field.…”
Section: Introductionmentioning
confidence: 99%